Chariots, mail coaches and wagons in the Arabic dialect of Qaṭrāyīth (“in Qatari”) in early Islamic eastern Arabia - Mario Kozah (22303852) (2024)
This paper will present the evidence for two newly discovered words, gawzag and shagar, meaning “two-horse chariot/mail coach” and “wagon” respectively in the eastern Arabian dialect of Qaṭrāyīth (Syriac for “in Qatari”) of the seventh and eighth centuries ce. They reveal the continued local knowledge of wheeled transport in Arabia and possible use long after its supposed disappearance in the Near East between the fourth and sixth centuries according to Richard Bulliet's well-known thesis in his seminal work The Camel and the Wheel (New York: Columbia University Press, 1990). The fact that this vernacular maintained two specific words for two different modes of wheeled transport likely suggests a practical need for them in everyday communication among the inhabitants of the Beth Qaṭraye region (Syriac for “region of the Qataris” in north-eastern Arabia). Moreover, their use in an Arabic dialect reveals that native words were developed for wheeled vehicles in the local language spoken by the inhabitants of the area well before the adoption of markabah as a neologism to mean chariot in nineteenth-century Arabic, according to Michael Macdonald's stimulating article “Wheels in a land of camels” (Arabian Archaeology and Epigraphy 20/2, 2009). Thus, the various rock drawings of two-wheeled carts and chariots in northern Arabia may in fact not only have been known but also used nearby in eastern Arabia, rather than being inaccurate representations reflecting a distant awareness of the existence of chariots elsewhere such as in Mesopotamia and Egypt as had been previously thought. This is a literary, philological. and historical study that aims at presenting newly discovered vocabulary in context for further analysis by linguists and others. Other Information Published in: Bulletin of the School of Oriental and African Studies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1017/s0041977x23000976